Konverter DC-DC Penstabil Tegangan Listrik Out Put Sel Surya Terhadap Perubahan Input Cahaya - Marpaung, Parlindungan Pandapotan (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The dc output voltage of the solar cell is regulated due to changes in the intensity of sunlight shining on the surface of the solar cell, so that in the treatment of storing the dc output voltage of the solar cell to an external electrical load energy saver becomes unstable. Testing the occurrence of regulation of the dc output voltage of the solar cell expressed as the Vo(cell) parameter is carried out by changing the distance of the white light intensity irradiation from the LED lamp to the surface of the solar cell. The research method of adding a dc-dc converter device to the output part of the solar cell produces a stable dc output voltage parameter from the dc-dc converter device. The results of the research on charging energy storage on HP charge batteries using (1) the output voltage supply without the dc-dc converter parameter Vo(cell) obtained the results of charging the electrical energy load of the hp charge battery at Wb1(bat.) = 1.408 watt.hours and ( 2) The use of the supply voltage output Vo(conv.) from the dc-dc converter results in charging the electrical energy load for charging the battery charge hp reaching Wb2(bat.) = 1.426 watt.hours. There is a difference in the length of time it takes for the results of electrical energy to fill the cell phone charge battery using an output voltage source supply originating from a dc-dc converter regulator compared to an output voltage source without using a dc-dc converter regulator.